A review of quality-of-life in elderly osteoarthritis. (21st April 2023) - Atukorala, Inoshi; Hunter, David J.
ABSTRACT: Introduction: Osteoarthritis (OA) is the commonest joint disease in the world. Although aging is not invariably associated with OA, aging of the musculoskeletal system increases susceptibility to OA. Pain and reduced function due to OA, negatively impact health-related quality of life (HRQoL) in the elderly. Areas covered: We searched PubMed and Google Scholar with search term "osteoarthritis' combined with terms 'elderly' 'ageing' 'healthrelated quality of life' 'burden' "prevalence 'hip osteoarthritis' 'knee osteoarthritis' 'hand osteoarthritis' to identify relevant articles. This article discusses the global impact and joint-specific burden due to OA and the challenges in assessment of HRQoL in elderly with OA. We further describe some HRQoL determinants that particularly impact elderly persons with OA. These determinants include physical activity, falls, psychosocial consequences, sarcopaenia, sexual health, and incontinence. The usefulness of physical performance measures, as an adjunct to assessing HRQoL is explored. The review concludes by outlining strategies to improve HRQoL. Expert opinion: Assessment of HRQoL in elderly with OA is mandatory if effective interventions/treatment are to be instituted. But existent HRQoL assessments have shortcomings when used in elderly§. It is recommended that determinants of QoL which are unique to the elderly, be examined with greater detail and weightage in future studies.